2023
DOI: 10.3390/su151914474
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Melt-Spun Biodegradable Fibers

Mohammadreza Naeimirad,
Bas Krins,
Gert-Jan M. Gruter

Abstract: The growing awareness of environmental issues and the pursuit of sustainable materials have sparked a substantial surge in research focused on biodegradable materials, including fibers. Within a spectrum of fabrication techniques, melt-spinning has emerged as an eco-friendly and scalable method for making fibers from biodegradable plastics (preferably bio-based), intended for various applications. This paper provides a comprehensive overview of the advancements in the realm of melt-spun biodegradable fibers. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 271 publications
0
7
0
Order By: Relevance
“…No adverse effects like sharkskin formation, development of stick–slip discontinuity (so-called “bambooing”), or occurrence of melt fractures (“corkscrewing”), problems frequently observed in melt-spinning, ,, were observed. The smooth surface and the fact that this was achieved even without extensive optimization of conditions underline the suitability of PE-18,18 for melt-spinning (cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No adverse effects like sharkskin formation, development of stick–slip discontinuity (so-called “bambooing”), or occurrence of melt fractures (“corkscrewing”), problems frequently observed in melt-spinning, ,, were observed. The smooth surface and the fact that this was achieved even without extensive optimization of conditions underline the suitability of PE-18,18 for melt-spinning (cf.…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to its above-ambient glass transition temperature, which hinders accessibility of the amorphous regimes for enzymatic breakdown. This is particularly relevant for textile applications because fibers abraded during washing of textiles are a major contributor to microplastics pollution. , Other types of synthetic fibers employed for textiles, like polyamides, polyethylene (HDPE), or polypropylene (PP), also offer no benefits over PET in terms of circularity and environmental persistence. Beyond these polymers, poly(lactide) (PLA) as a biobased polyester has also been established as a fiber material, and further, biodegradable polyesters that are most prominently applied in films and packaging plastics have been studied in the form of fibers [like poly(butylene-adipate- co -terephthalate), PBAT; poly(hydroxy-butyrate- co -valerate), PHBV; and polycaprolactone, PCL]. , However, their overall profile of processability and fiber performance, in many instances, remains unsatisfactory. Often, their rather soft or brittle nature is problematic already.…”
Section: Introductionmentioning
confidence: 99%
“…Materials based on commercially available monomers, such as polyester-2.18, 2 open the door for larger-scale developments and applications. Areas of interest comprise food packaging films and textile fibers, 62 to name only two examples. Further studies among others should address, for a given long-chain polyester, upscaling and optimization with regard to the molecular weight of polymerization procedures, elaboration of melt rheologies and crystallization rates depending on polymer microstructure, the necessity of stabilization, and the optimization of processing parameters as well as key material properties for a given application.…”
Section: Discussionmentioning
confidence: 99%
“…The biodegradability of polymers is dependent on multiple different parameters, including thermal properties, polymer structure, degree of crystallinity and hydrophilicity. 28,55,56 In the previous sections, it was shown that the polymeric properties can be tailored by varying the length of the aliphatic comonomer in BHMF-based polyesters. Furthermore, the hydrophilic character of the polyester surfaces is expected to be beneficial for biodegradation.…”
Section: Biodegradationmentioning
confidence: 99%